Pengaruh manajemen risiko, modal intelektual dan inovasi terhadap nilai perusahaan dimediasi kinerja perusahaan - Dinna Riyani; Lilis Ardini; Suwardi Bambang Hermanto (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aimed to examine the effect of risk management, intellectual capital, and innovation on firm value with companies’ performance as mediating variable. The population was LQ-45 companies that were listed on Indonesia Stock Exchange (IDX) from 2017-up to 2020. Furthermore, the data collection technique used purposive sampling. There were 180 data that were taken from LQ-45 companies’ annual reports and published in www.idx.co.id. Moreover, the data analysis technique used both inner and outer models with Partial Least Square 3.0. The result concluded that (1) Risk Management, Intellectual Capital, and Innovation did not affect the firm value, (2) Risk Management and Innovation had a positive effect on the companies’ performance, (3) Intellectual Capital did not affect on the companies’ performance, and (4) the company’s performance could not mediate the relationship among risk management, intellectual capital, and innovation on the firm value.